Utilization and efficacy of elbasvir/grazoprevir for treating hepatitis C virus infection after liver transplantation. Issue 12 (19th July 2018) - Miuma, Satoshi; Miyaaki, Hisamitsu; Soyama, Akihiko; Hidaka, Masaaki; Takatsuki, Mitsuhisa; Shibata, Hidetaka; Taura, Naota; Eguchi, Susumu; Nakao, Kazuhiko
Abstract : Aim: Recently, elbasvir/grazoprevir combination therapy (EBR/GZR) was reported to have excellent antiviral effects for chronic genotype 1 hepatitis C virus (HCV) infection. However, it has not been recommended for patients with post‐liver transplant (LT) HCV re‐infections because of a lack of evidence for effectiveness and drug–drug interactions. Methods: We report the usage of EBR/GZR in five post‐LT HCV re‐infected patients with the kinetics of renal function and tacrolimus trough levels during and after therapy. Furthermore, to evaluate the antiviral effects, we examined the HCV kinetics during and after therapy and compared this with other interferon‐free therapy in post‐LT patients ( n = 19). Results: All patients treated with EBR/GZR therapy obtained rapid virologic response and sustained at 12 weeks post‐treatment. There was no evidence of worsening estimated glomerular filtration rates. Three patients were given tacrolimus as immunosuppressive therapy and its trough levels were controllable with dosage adjustments. One patient developed grade 1 diarrhea 3 days after therapy induction. To evaluate the antiviral effects of EBR/GZR therapy for these patients, we compared them to the effects of daclatasvir/asunaprevir combination therapy ( n = 8) and sofosbuvir/ledipasvir combination therapy ( n = 11). The EBR/GZR combination was not inferior to other therapies in its early phase and late‐phase antiviral effects. Conclusions: Although further studies with a larger number of patients are required, we suggest that EBR/GZR therapy is an alternative therapy for patients with post‐LT genotype 1 HCV re‐infection.